Knowledge, Attitude and Practices of Dentists Towards the Dental Treatment of Epileptic Patients - Maham Qasim, Ayesha Sufiyan, Maryam Shaukat, Sarah Rabbani, Amna Nauman Khan, Nauman Rauf Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
The objective of this study is to investigate the level of knowledge, attitude and practices of final year students, house officers and demonstrators towards the epileptic patients visiting Sharif Medical and Dental College. A well-formed proforma was used to document the knowledge of dental health care providers regarding the dental treatment of patients with epilepsy. 170 participants were included in the study out of which 119 were male and 51 were female. Most of the respondents agree that epilepsy cannot be identified on history alone. 48.2% think that epileptic patients can be treated in-office safely. 54.7% of respondents believe. Significant improvement of dentists’ knowledge regarding epilepsy is mandatory as insufficient knowledge of dentists about epilepsy may drastically affect their treatment proficiency